Genome sequence of acinetobacter baumannii AC12, a Polymyxin-Resistant Strain Isolated from Terengganu, Malaysia - Gan, H.M.; Lean, S.S.; Suhaili, Z.; Thong, Kwai Lin; Yeo, C.C. (2012)
Acinetobacter baumannii is a major cause of nosocomial infection worldwide. We report the draft genome sequence of A. baumannii AC12, a multidrug-resistant nosocomial strain with additional resistance to carbapenems and polymyxin. The genome data will provide insights into the genetic basis of antimicrobial resistance and its adaptive mechanism.